Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

If g(x) = -3x – 4 and h(x) = –22 + x, find g(h (8)).


Sagot :

Answer:

g(h(8)) = 38

Step-by-step explanation:

Hello!

Work from inside to out. First find h(8):

  • h(x) = -22 + x
  • h(8) = -22 + 8
  • h(8) = -14

Now, plug in -14 for g(x). Remember, we are working inside to out.

  • g(x) = -3x - 4
  • g(-14) = -3(-14) - 4
  • g(-14) = 42 - 4
  • g(-14) = 38

So, g(h(8)) is 38.